Prevalence and factors associated with musculoskeletal disorders among primary and secondary school teachers - Gikaro, John Marwa; Goi, George Claud; Taamala, Farida Hassan; Hamadi, Hussein Hamisi; Welema, Jenifa Charles; Minduva, Zakia Mussa; Swai, Elia Asanterabi (Frontiers in Public Health, 2025)
BackgroundMusculoskeletal disorders (MSDs) are among the top conditions that affect the working population including teachers. Historically, Kilimanjaro region including Moshi municipal, has been a pioneer in education development in Tanzania. Moshi municipality represent a diverse setting of primary and secondary education; however, no study has yet examined MSDs among teachers in this setting.ObjectiveThe aim of this study was to investigate the prevalence of MSDs among primary and secondary school teachers, and identify the associated factors.MethodologyA cross-sectional study was conducted among 205 primary and secondary school teachers in Moshi Municipal, Northern Tanzania. Data was collected using a structured questionnaire that incorporated the Standardized Nordic Musculoskeletal Questionnaire (SNMQ). Logistic regression model was used to estimate the factors associated with MSDs.ResultsThe 12-month and 7-day prevalence of MSDs in one or more body sites was 61.5% and 44.4%, respectively. Twelve-month prevalence was higher in the lower back (44.4%), followed by the neck (31.2%), upper back (26.8%), and shoulders (18.5%). Seven-day prevalence was higher in the lower back (29.8%), followed by the neck (16.1%), ankles/feet (12.2%), and upper back (9.8%). Predictors of MSDs at different body parts were the age, gender, BMI, working duration, number of working hours, number of classes, and number of students in class.ConclusionOccupational factors significantly contribute to MSDs among teachers. Complying to recommended workload for teachers may help to prevent MSDs in teaching profession.